Pengaruh Cara Economic Value Added (EVA), Market Value Added (MVA) Dan Debt To Equity Ratio (DER) Kepada Kinerja Keuangan Pada Perusahaan Manufaktur Food And Beverages Yang Terekam Di BEI Periode 2017-2019 - Firmansyah, Rudy Wahyu; Wahono, Budi; Nurhidayah, Nurhidayah (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This research aims to determine whether economic value (X1), economic added value (EVA), market added value and debt to equity ratio (DER) are related to the financial performance of food products. included on the IDX in 2017. and connected beverage companies -2019. Using the same type of research method. Combining study information means conveying it quantitatively. The research information linkage problem approach is presented in numerical form when the research information linkage problem is analyzed. The research results show that economic added value (EVA), market added value and debt to equity ratio (DER) are simultaneously related to the financial performance of food and beverage companies included in the 2017-2019 BEI. Economic added value (EVA). ) is partially related to the financial performance of food and beverage companies that are members of the BEI during 2017-2019. Financial performance of food and beverage companies that are members of the BEI during 2017-2019. The debt to equity ratio (DER) is partly related to the financial performance of food and beverage companies listed on the IDX during 2017-2019. Keywords: Economic Value Added (EVA), Market Value Added and Debt to Equity Ratio (DER).